Developing organizational agility in SMEs: An investigation of innovation's roles and strategic flexibility - I Wayan Edi Arsawan; Ni Kadek Dessy Hariyanti; I Made Ari Dwi Suta Atmaja; Dwi Suhartanto; Viktor Koval (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Although social capital and collaborative knowledge creation were considered essential drivers in maintaining competitive advantage, empirical evidence on the impact of collaborative knowledge creation on organizational agility remained limited. Therefore, this study examined the relationship between social capital and collaborative knowledge creation in building innovation and agility and testing strategic flexibility as a moderating variable. It employed a quantitative design by distributing questionnaires to 414 managers and assistant managers of SMEs analyzed by SmartPLS-SEM. The results showed that social capital significantly affected collaborative knowledge creation, innovation, and organizational agility. Meanwhile, collaborative knowledge creation has no significant impact on organizational agility. Furthermore, strategic flexibility was not a moderating variable of the relationship between innovation and organizational agility. Based on these findings, this study produced recommendations for managers to strengthen organizational agility.
Keywords: 650; innovation; collaborative knowledge creation; organizational agility; social capital; strategic flexibility